Pengaruh Social Media Content Terhadap Re-Purchase Intention dengan E-Wom dan Interactivity Sebagai Variabel Intervening - Steven Dava Rivaldy Yohanes; Tarandhika Tantra (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The development of technology, especially social media today, has had a major impact on activities in a business, especially in terms of competition. This study aims to investigate the relationship between social media content and consumer repurchase intentions. In addition, it was determined whether E-WOM and interactivity can act as mediating variables between social media content and repurchase intention. Data was collected through an online questionnaire and the study was conducted in the city of Bandung. A total of 150 valid questionnaires were obtained and analyzed functioning Partial Least Square Structural Equation Modeling (PLS-SEM) through WarpPLS 7.0 software. Based on the results of the path coefficient values, the findings positively support the direct effect of social media content on repurchase intention of 0.257, social media content on e-wom 0.681, social media content on interactivity 0.729, e-wom on repurchase intention of 0.290, interactivity on repurchase intention 0.270. In addition, the results of this study confirmed the positive effect of the mediating role of e-wom between social media content and repurchase intention of 0.284 and this study had a positive effect on the mediating role of interactivity between social media content and repurchase intention of 0.316. This study shows some managerial implications for food and beverage businesses and provides a fundamental strategy related to their social media.